2019
DOI: 10.1016/j.bbrep.2019.100656
|View full text |Cite
|
Sign up to set email alerts
|

The primitive growth factor NME7AB induces mitochondrially active naïve-like pluripotent stem cells

Abstract: Naïve pluripotent stem cells (PSCs) display a distinctive phenotype when compared to their “primed” counterparts, including, but not limited to, increased potency to differentiate and more robust mitochondrial respiration. The cultivation and maintenance of naïve PSCs have been notoriously challenging, requiring the use of complex cytokine cocktails. NME7 AB is a newly discovered embryonic stem cell growth factor that is expressed exclusively in the first few days of human blastocyst dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This study indicated that MTCH2 is important for elongated mitochondria which itself was sufficient for driving naïve-toprimed interconversion by altering histone deacetylation and nuclear gene reprogramming (Bahat et al, 2018). In addition, recent work has demonstrated that supplementation with a recombinant truncated human NME7 (NME7 AB ) is sufficient to induce a stable naïve-like state in hPSCs (Carter et al, 2016) associated with reactivation of mitochondrial function and stimulation of ATP production (O'Reilly et al, 2019).…”
Section: Mitochondrial Metabolismmentioning
confidence: 89%
“…This study indicated that MTCH2 is important for elongated mitochondria which itself was sufficient for driving naïve-toprimed interconversion by altering histone deacetylation and nuclear gene reprogramming (Bahat et al, 2018). In addition, recent work has demonstrated that supplementation with a recombinant truncated human NME7 (NME7 AB ) is sufficient to induce a stable naïve-like state in hPSCs (Carter et al, 2016) associated with reactivation of mitochondrial function and stimulation of ATP production (O'Reilly et al, 2019).…”
Section: Mitochondrial Metabolismmentioning
confidence: 89%